2021
DOI: 10.3390/jof7100860
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analyses of Amphotericin B Susceptibility in Aspergillus fumigatus

Abstract: Aspergillus fumigatus is a ubiquitous saprophytic mold that can cause a range of clinical syndromes, from allergic reactions to invasive infections. Amphotericin B (AMB) is a polyene antifungal drug that has been used to treat a broad range of systemic mycoses since 1958, including as a primary treatment option against invasive aspergillosis in regions with high rates (≥10%) of environmental triazole resistance. However, cases of AMB-resistant A. fumigatus strains have been increasingly documented over the yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…Together, mutations in other genes and epigenetic mechanisms or interactions among multiple genes may play important roles in antifungal drug resistance in C. glabrata. Similar mechanisms for drug resistance have been demonstrated in several other fungi, including triazole resistance in C. albicans and amphotericin B resistance in A. fumigatus [104,105].…”
Section: Discussionsupporting
confidence: 64%
“…Together, mutations in other genes and epigenetic mechanisms or interactions among multiple genes may play important roles in antifungal drug resistance in C. glabrata. Similar mechanisms for drug resistance have been demonstrated in several other fungi, including triazole resistance in C. albicans and amphotericin B resistance in A. fumigatus [104,105].…”
Section: Discussionsupporting
confidence: 64%
“…Together, these results suggested that different agricultural fungicides likely selected for different resistance mechanisms and that some of these mutations may make them more susceptible to other drugs. Allelic swaps and/or genetic crosses are needed in order to determine the quantitative contributions of each of these observed mutations to triazole susceptibilities ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional investigations using targeted mutagenesis, allele swaps, and/or genetic crosses are needed in order to determine their specific contributions to differences in triazole susceptibilities in A. alternata (e.g., 18, 19, 40, 42, 67, 68). Furthermore, whole-genome sequencing and genome-wide association studies of populations of strains with different MICs could help identify additional mutations outside the cyp51 gene that are associated with triazole susceptibilities in A. alternata ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are no studies reporting genetic mutational changes leading to increasing amphotericin B MICs. Genetic analysis of amphotericin B resistant A. fumigatus isolates identified missense variants in genes tcsB, mpkC and catA and mutations in fumarylacetoacetate hydrolase associated with amphotericin B resistance [ 91 , 92 ]. There are observations of resistant Aspergillus spp.…”
Section: Purpose Of Reviewmentioning
confidence: 99%